Principles and Applications of Interfacial Rheology in (Pre)Formulation Development of Pharmaceutical Preparations - Krstonošić, Veljko; Pavlović, Nebojša; Ćirin, Dejan (Archives of Pharmacy, 2023)
Rheology is a science that deals with the movement and deformation of materials, while interfacial rheology is a branch of rheology that focuses on the study of the mechanical properties of fluid interfaces, such as liquid-liquid and liquid-gas interfaces. The behavior of fluid interfaces differs significantly from that of bulk materials, and standard rheological measurements of bulk materials cannot adequately describe their properties. Interfacial rheology is a specialized approach to the study of viscoelasticity and interfacial tension at liquid interfaces and provides valuable insight into intermolecular interactions and surface forces. This knowledge is particularly important for the development of advanced formulations and systems with tailored properties and functionalities. Interfacial rheology is a rapidly growing research field with diverse applications in science and industry. It plays a pivotal role in the development and optimization of pharmaceutical formulations and design of innovative drug delivery carriers with improved stability, enhanced drug release profiles, and targeted delivery capabilities. This review article aims to provide a comprehensive overview of interfacial rheology, its principles, measurement techniques, and applications in various industries. By exploring recent advancements and emerging trends in the field, we aim to highlight the significance of interfacial rheology in optimizing formulations, enhancing product performance, and driving innovations, particularly in pharmaceutical science.
Keywords: interfacial rheology; viscoelasticity; emulsion; foam; preformulation